Inheritance law as a contractual modality - Ackermann Miranda, Behni (2021)
Succession is a legal act by which all assets, rights and obligations of a person are   transmitted to others because of his death. In our national law, it is not legislated in any of its forms including the legislature considers his dangerousness to the right of the heirs estimating that the other party may desire the death of the deceased soon for the contract to take effect. This rating does not extend to other contracts whose effects are equally subject to the death of de cujus such as life insurance contract or annuity contract.